Relevansi Nilai-Nilai Islam Nusantara dalam Kajian Perspektif Hadis - Sabri, Muhammad; Sapri, Yohanes (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2024)
In negative accusations about the narrative of Islam Nusantara, conflict embryos arise in society. So it is interesting for the writer to explore the relevance of Nusantara Islamic values in the study of hadith. The formulation of the problem of this research is, how is the typology of the Prophet in accepting the cultures of his time, and how is the compatibility of the paradigm of Islam Nusantara with the hadith of Rasulullah SAW. The data sources for this research are hadith books, books, scientific papers, articles, and websites related to the theme of the discussion. The data collection technique is by collecting material manually and through mass media such as Google Scholar, Google Books, and other media whose credibility can be trusted. The data analysis techniques in this research are reading, studying, analyzing, reducing, and then drawing conclusions to get new information from a study. The findings are, the way Rasulullah SAW treats culture, namely, first, revising culture in the direction of Islamic values. Second, explicitly reject a culture that is entirely contrary to Islamic teachings. Third, accept a culture if it does not conflict with Islamic teachings. Furthermore, the Islam Nusantara syllogism is relevant or compatible with the way the Prophet perceived the culture that developed in his time.